+0  
 
0
267
2
avatar

(3p-9)(p+2)

Guest Apr 22, 2017
 #1
avatar+18 
0

(3p-9) (p+2)

3p (p+2) -9 (p+2)

3p^2+6p-9p-18

3p^2-3p-18

Dividing through out by 3,we get;

3p^2/3 - 3p/3 - 18/3

P^2 - p - 6

(P - 3) (p+2)

P - 3 =0 OR P+2=0

P - 3 +3=0+3  OR P+2 - 2=0 - 2

P=3                 OR   P= -2

Pills  Apr 22, 2017
 #2
avatar
0

But in the original problem it doesnt ever say that its equal to zero though???

Guest Apr 23, 2017

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.